The Infuence of City Branding Towards City Image: The Case Study of Tourism Destinations in Yogyakarta City, Special Region of Yogyakarta, Indonesia - Endhar Widjaya Putra; Edy Yulianto; Andriani Kusumawati (Sekolah Pascasarjana Universitas Brawijaya, 2019)
The main purpose of this study is to understand the influence of city branding toward city image and its impact on the intention to visit and decision to visit. The samples used in this study were 280 domestic visitors there is a tourism desti-nation in Yogyakarta City and they aware of â€œJogja istimewaâ€ as a brand of Yogyakarta City. It is the destination tourism that located on seven destinations consist of Keraton Yogyakarta, Pagelaran Keraton, Malioboro, Museum Benteng Vredeburg, Taman Sari, Taman Pintar, and Gembira Loka Zoo. Structural Equation Model (SEM) base on Partial Least Square (PLS) is used to analyze and measure the degree between the independent variable and dependent variable. The findings revealed that city branding has a significant effect toward city image and intention to visit, however city brand-ing also influenced on decision to visit incidentally. Moreover, it indicates that city image has a significant effect on intention to visit and decision to visit. Last but not least, the intention to visit has a significant effect on decision to visit.